Characterisation of pregnancy-induced alterations in apolipoproteins and their associations with maternal metabolic risk factors and offspring birth outcomes: a preconception and longitudinal cohort studyResearch in context - Li Chen; Karen Mei-Ling Tan; Melvin Khee-Shing Leow; Kok Hian Tan; Jerry Kok Yen Chan; Shiao-Yng Chan; Yap Seng Chong; Peter D. Gluckman; Johan G. Eriksson; Markus R. Wenk; Sartaj Ahmad Mir (EBioMedicine)
Summary: Background: Apolipoproteins as an integral part of lipoproteins are crucial for the transport and metabolism of lipids. However, there is a lack of longitudinal studies to quantify the concentrations of maternal apolipoproteins from preconception to postpartum and their associations with maternal metabolic health and offspring birth outcomes. Methods: Quantification of apolipoproteins was performed on maternal plasma samples (N = 243 trios) collected at preconception, 26–28 weeks’ pregnancy, and three months postpartum in the Singapore PREconception Study of long-Term maternal and child Outcomes (S-PRESTO) cohort study. Linear regression models and network analysis were implemented to investigate the association of apolipoproteins with maternal genetic variants, biochemical measures, metabolic risk factors, and offspring birth outcomes. Findings: The concentrations of ApoC-III, ApoB and ApoL1 substantially increased in pregnancy compared to preconception and postpartum. Genome-wide association studies (GWAS) identified multiple single-nucleotide polymorphisms (SNPs) associated with plasma apolipoproteins (P < 5.00E-08), including APOE-rs7412 for ApoE, LPA-rs56393506 for Apo(a), APOM-rs707921 for ApoM, ABCC4-rs117797426 for ApoJ, THSD7B-rs575613 for ApoA-II, and LOC102724443-rs140433245 for ApoA-IV. Plasma apolipoproteins were strongly associated with biochemical measures including lipidomic profiles, lipoprotein features and fat-soluble vitamins, as well as metabolic risk factors including glycaemic traits, liver enzymes, inflammatory markers, albumin, and blood pressure. Integrative network analysis of apolipoproteins and their correlates/determinants revealed both shared and specific associations, with the strongest relationships observed among apolipoproteins, cholesterol, triglycerides, alpha tocopherol, and GlycA (Padj < 0.05). Higher maternal ApoC-I and ApoC-III concentrations at preconception were significantly associated with shorter gestational age of the offspring. Interpretation: We describe the longitudinal landscape of maternal circulating apolipoproteins from preconception to postpartum and their associations with maternal metabolic risk factors and offspring birth outcomes. This multi-omics characterisation of biochemical correlates and genetic determinants of maternal apolipoproteins will deepen our understanding of the molecular basis of metabolic flexibility in expectant mothers, leading to better assessment of pregnancy-related outcomes. Funding: This research was supported by the Singapore National Research Foundation under its Translational and Clinical Research (TCR) Flagship Programme and administered by the Singapore Ministry of Health's National Medical Research Council (NMRC), Singapore- NMRC/TCR/004-NUS/2008; NMRC/TCR/012-NUHS/2014. The Singapore Lipidomics Incubator (SLING) is supported by grants from the National University of Singapore via the Life Sciences Institute, the National Research Foundation (NRF, NRFI2015-05 and NRFSBP-P4) and A∗STAR IAF-ICP I1901E0040. Additional funding is provided by Institute for Human Development and Potential (IHDP)—Agency for Science, Technology and Research (A∗STAR), Singapore.